Efektivitas Penggunaan Film Berbahasa Inggris Sebagai Media Pembelajaran Dalam Meningkatkan Listening Skill Mahasiswa - Umi Imtitsal Rasyidah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The purpose of this study is to find out how effective the use of movies is in improving students' listening skills in the field of English studies, and also to find out students' perspectives on the use of movies as a learning medium. The movie used in the research is an animation titled Sonic The Hedgehog which tells about the adventures of aliens on earth with a human. The method used is quantitative descriptive method using interviews and observations. From the results conducted on listening course lecturers and twenty-three second semester students at the Faculty of Education, Tribakti Islamic University Lirboyo Kediri found that the use of English films in improving students' listening skills is very effective. According to the students' perspective, the use of this movie really helps them in learning.